2018
DOI: 10.1037/rep0000245
|View full text |Cite
|
Sign up to set email alerts
|

Towards an integration of the health promotion models of self-determination theory and theory of planned behavior among people with chronic pain.

Abstract: Despite preexisting pain and functional disability, the findings suggest that health behavior factors from both SDT and TPB are associated with physical activity and exercise participation. This line of research should encourage rehabilitation professionals to recommend regular physical activity and exercise, while simultaneously addressing and monitoring the SDT and TPB factors that are well-timed and appropriate for persons with chronic pain through motivation-oriented rehabilitation approaches. (PsycINFO Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 51 publications
(79 reference statements)
2
11
0
Order By: Relevance
“…Oppositely, the external regulation and introjected regulation, along with amotivation, have been related with negative consequences, such as boredom and unhappiness [15]. Moreover, more self-determined forms of motivation predict both the intention to be physically active, and the actual behaviour [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Oppositely, the external regulation and introjected regulation, along with amotivation, have been related with negative consequences, such as boredom and unhappiness [15]. Moreover, more self-determined forms of motivation predict both the intention to be physically active, and the actual behaviour [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, a meta-analysis of SDT related to a broad range of health contexts demonstrated that it is a viable conceptual framework in which to study antecedents and outcomes of motivation for health-related behaviours [33]. Such findings suggest that SDT could become a foundation for the development of self-management interventions within health promotion and healthcare contexts, including those which promote PA [29,34]. Thus, efforts by healthcare professionals (GPs, Orthopaedic Consultants, Physiotherapists) to promote joint health, wellbeing and quality of life might benefit from including principles of SDT in delivering their messages.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst there are still relatively few studies directly applying SDT to populations with COPD (McCullough et al, 2016 ; Richardson et al, 2014 ), research has reported the ability of the theory to predict behaviours relevant to COPD self-management, albeit in non-COPD populations (Ng et al, 2012 ; Ntoumanis et al, 2020 ; Ryan, Patrick, Deci, & Williams, 2008 ); including successfully predicting physical activity participation (Brooks et al, 2018 ; Rahman, Thøgersen-Ntoumani, Thatcher, & Doust, 2011 ; Rahman, Hudson, Thøgersen-Ntoumani, & Doust, 2015 ) and smoking cessation (Williams et al, 2006 ). Multiple studies have also found that higher levels of basic need satisfaction were associated with greater well-being and perceived health (Bartholomew et al, 2011b ; Chen, Chang, Tsai, & Hou, 2018 ; Rahman et al, 2011 ; Rahman et al, 2015 ).…”
Section: Main Textmentioning
confidence: 99%